I'll explain the Maths one. (You can use a ^ to signify 'to the power of')

Letx = 5(for illustration. x will remain 5 for the whole exercise)

f(x) = - x^2

f(x) is a function which takes any value (x), squares it, then negates it.

So, if x = 5, f(5) = - x^2 = -25

In this case, x-2 is 5-2 = 3, so f(3) = -9

So f(x-2) = -9

And y = -(x-2)^2 = - (5-2)^2 = -(3)^2 = -9

So f(x-2) = y = -(x-2)^2

But put simpler, you can substitute anything for x

If you change f(x) to f(x-2), then -x^2 becomes - (x-2)^2, which is y.

And it even works without colours!